Construction Network Based On Cluster Organization Ways Of Effective Management - Buranov Olmas; Sh.B. Abdusamatov (Genius Journals, 2022)
Due to the importance of the construction industry in the development of the world economy, extensive scientific research is being carried out to ensure the sustainable development of construction enterprises. This article focuses on new approaches to improving the construction industry, considering it as an important factor in the development of the construction industry based on the cluster model, and also provides suggestions and recommendations for organizing the cluster model.
Keywords: construction industry; cluster model; innovation; modernization